دراسة بيولوجيا التكاثر عند الجمبريMarsupenaeus japonicus ((Decapoda, Penaeidae في شاطئ اللاذقية - عمار, ازدهار; عيد, أيهم (Latakia University Journal -Biological Sciences Series, 2013)
هدفت الدراسة إلى تحديد أوقات التكاثر والنضج الجنسي للجمبري Marsupenaeus japonicus في شاطئ اللاذقية كمقدمة لتفريخه واستزراعه. جمعت أفراد النوع من المياه البحرية في منطقة ابن هاني شمال اللاذقية خلال الفترة الممتدة من شهر تشرين الثاني2010 وحتى شهر تشرين الأول 2011 بمعدل مرة أو مرتين شهرياً. شملت الدراسة المخبرية التمييز بين الذكور والإناث لجميع الأفراد و إجراء القياسات المورفومترية لها و تحديد الوزن، ثم تحديد مرحلة نضج المبايض خارجياً وتشريحياً. سيطرت الإناث خلال معظم فترة الدراسة و بلغت نسبتها في العينات 64% و قد راوحت أطوالها بين 105 – 230 مم, في حين بلغت نسبة الذكور 36% و قد تراوحت أطوالها بين 100 – 177 مم , و أظهرت الدراسة أن طول الدرقة لـ 50% من الإناث عند أول نضج جنسي لها هو 66 مم, و تشير القيم المتوسطة لمؤشر النضج الجنسي GSI اإلى وجود ذروتين لـ GSI تدلان على فترتي تكاثر خلال السنة لدى النوع المدروس في فصلي الخريف والربيع. The aim of study was to determine the dates of breeding and sexual maturity for Marsupenaeus japonicus in Lattakia coast as introduce for hatching and culturing it. The specimens were collected from the sea water of Ibn-Hany area at the north of Lattakia, during the period November 2010 to October 2011 once or twice monthly. In vitro study included distinguishes males and females, morphometric measurements and weights for all individuals. The genital maturity stage was determined externally and through histological sections. Females were dominants through the period of study, with percentage 64%, while their lengths were between 105-230 mm. Males percentage were 36%, and their length ranged 100-177 mm. The study showed that carapace length for half of the females was 66 mm on their first sexual maturity. The mean values of gonadsomatic index GSI showed two picks indicate to two spawning peaks during the year for the studied subject in Autumn and Spring .